REFORMASI MANAJEMEN PELAYANAN PUBLIK MENUJU GOOD GOVERNANCE - Heffy, Mutroni (Pusjar SKPP Lembaga Administrasi Negara, 2009)
Reformation on public service management which will lead to the implementation of good governance requires the improvement on the given service quality which in accordance with community needs and desires. In providing public services, the standardized service is one of the most important aspect that must be set, and the authorized bureaucracy must have a transparent and fair responsibility to the public in order to create an excellent service which actually is one of the indicator of good governance and the measurement of the success of regional autonomy implementation. Keywords: new public service, public services, good governance